2014
DOI: 10.5376/mpb.2014.05.0003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variation in Indian Mustard (<i>Brassica juncea</i> L.) Using PCR Based Markers

Abstract: Indian mustard (Brassica juncea L.) is an important oilseed crop with oil content ranging from 30 to 48 percent. However, presence of high erusic acids, glucosinolates and saturated fatty acids and also narrowed genetic base of existing varieties confines its use. The present investigation was undertaken to explore the diversity among Indian mustard genotypes (varieties) using molecular markers. We used RAPD and EST based SSRs as the markers for assessment of genetic variation among 23 genotypes of Brassica ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
9
2
Order By: Relevance
“…In our study, the average PIC values were found to be higher than that of reported by Turi et al, (2012) in B. juncea (0.46). Gupta et al, (2014) reported low PIC value 0.281; Sudan et al, (2016) PIC values ranged from 0.12-0.61 with an average to 0.314 but lower than that, observed by Nanjundan et al, (2015). ) observed by Avtar et al, (2016) were found to be higher than that of our study.…”
Section: Genetic Diversity Evaluation Studiescontrasting
confidence: 57%
“…In our study, the average PIC values were found to be higher than that of reported by Turi et al, (2012) in B. juncea (0.46). Gupta et al, (2014) reported low PIC value 0.281; Sudan et al, (2016) PIC values ranged from 0.12-0.61 with an average to 0.314 but lower than that, observed by Nanjundan et al, (2015). ) observed by Avtar et al, (2016) were found to be higher than that of our study.…”
Section: Genetic Diversity Evaluation Studiescontrasting
confidence: 57%
“…The average PIC value (0.519) observed in our study was consistent with previous estimates of SSR marker analysis in Indian mustard by Avtar et al (2016) [2] and Patel et al (2018) who reported average PIC values of 0.529 and 0.555, respectively. On the other hand, the observed value was higher than the values of 0.46, 0.28 and 0.31 reported by Turi et al (2012) [20] , Gupta et al (2014) [5] , and Sudan et al (2016) [17] , respectively.…”
Section: Results and Discussion Ssr Marker-based Divergence And Allelic Diversity Analysiscontrasting
confidence: 70%
“…In this study using ISSR markers, the rate of polymorphism was obtained as 88.75% and the number of polymorphic bands per primer was 20.29. In another study conducted in B. juncea, polymorphism rate and the number of polymorphic bands per primer were 91.2% and 15.73, respectively (Gupta et al, 2014). Furthermore, Abdelmigid et al (2012) showed that the polymorphism rate was 87% and the number of polymorphic bands per primer was 13.4 in B. napus.…”
Section: Discussionmentioning
confidence: 94%